Strategi Self Management Model Yates dan Model Cormier Terhadap Pengembangan Self Outonomy ditinjau dari Pola Asuh - Setiawan, Gede Danu; Dharsana, I Ketut (Bisma The Journal of Counseling, 2018)
This study aimed to analyze: Self autonomy differences between students who take the Self techniques and techniques Yates Model Managament Managament Model Self Cormier, who in terms of parenting parents. The design of the posttest- desaign with 2 x 2 factorial design used in this study. The sample was 60 students of class X SMA Negeri 2 Singaraja. The results showed that: (1) There are differences between the Self autonomy of students who take the theory of behavioral counseling techniques Yates Self Managament Model with students who follow the theory of behavioral counseling techniques Self Managament Model Cormier. (F = 6642, p <0.05). (2) There is a difference Self autonomy students are nurtured with parenting acceptance to students who cared parenting rejection. (F = 11 714; p <0.05). (3) There is an interaction effect between the theory of behavioral counseling and parenting parents against Self autonomy. (F = 17.98; p <0.05). (4) There are differences between students Self autonomy raised by parenting acceptance to students who cared parenting rejection after following the techniques of behavioral theory Self Management Model Yates. (F = 5,008; α <2.048). (5) There is a difference between student autonomy Self nurtured with parenting acceptance to students who cared parenting rejection after following the techniques of behavioral theory Self Management Model Yates. (F = 7,008; α <2.048). (6) There is a difference between student autonomy Self nurtured with parenting acceptance that follows the theory of behavioral techniques Yates Self Management Model with students who take the Self Management Model Cormier. (F = 3,861; α 2048). (7) There is a difference between student autonomy Self nurtured with parenting rejection that follows the theory of behavioral counseling techniques ModelYates with the Self Management Self Management Cormier follow techniques. (F = 2,252; α <2.048)